The invisible institution: how cultural norms perpetuate corruption in Malaysia’s civil service - Farhana, Farhana; Yaakob, Ahmad Faiz; Tunku Nashril-Abaidah, Tunku Nashril-Abaidah (2025)
Malaysia is renowned for its rich cultural diversity, which forms the foundation of its national identity. However, traditional values such as loyalty to the community and respect for hierarchy have been deeply embedded in daily life, potentially influencing institutional practices and governance outcomes. Despite numerous anti-corruption efforts implemented through institutional, legal and policy approaches, the latest report by Transparency International (2023) indicated that Malaysia's progress in combating corruption remained slow and inconsistent. This situation raised a critical question: why formal reforms have yet to produce substantial and sustained results. In response, this study seeks to explore how cultural norms play a role in sustaining and normalising corrupt practices within Malaysia’s civil service. Specifically, it aims to identify how culturally embedded informal institutions interact with formal mechanisms in shaping corruption outcomes. Employing a qualitative research design, the study draws on secondary data sources, including academic literature, policy documents, news media and recorded interviews with key figures such as the Inspector-General of Police, former Chief Commissioner of the Malaysian Anti-Corruption Commission (MACC) and directors of anti-corruption organisations. The findings suggest that cultural norms have a significant influence on the persistence of corruption, sometimes even outweighing the power of laws and official regulations. This study contributes to a deeper understanding of how corruption is embedded within social structures and proposes public sector reform strategies that are more sensitive to local cultural contexts.